Austerity, luxury and uncertainty in the Indian emerald trade - Brazeal, Brian (Journal of material culture, 2017)
This article examines the bodily practices of austerity in a Jain community that dominates a large portion of the international emerald trade. The material characteristics of emeralds make them refractory towards formal markets. These gemstones are impossible to value with consistency. Prices fluctuate wildly as the stones move from hand to hand and from continent to continent. Among the Jains, bonds forged by kinship and religious observance guarantee international, multi-million dollar contracts in the absence of any legal enforcement mechanism. Religious ethics ensure that people deal with each other in good faith and make good on their debts. These ethics are inculcated in part through bodily practices. The bodily practices of Jain traders also include jewelers’ sensual relationships with the stones themselves. The pursuit of salvation through austerity and the pursuit of profit through luxury are conjoined in a community dedicated to making sense of the inscrutable mineral characteristics of emeralds.